Promoting resource conservation, agri-food, and biodiversity through social value creation and community-based entrepreneurship - Korneeva Elena; Alekseeva Natalia; Cheremukhina Oxsana (BIO Web of Conferences)
This article focuses on promoting resource conservation, agri- food, and biodiversity with the idea of social value creation applied to community-based entrepreneurship. The main idea of this research is to examine the meaning of social value for social businesses explained through tourism-based entrepreneurship. Thus, special attention is given to the problems of local, marginalized, and impoverished communities that often lack the global attention of sustainable debates. The analysis is supported by three cases of social value creation by social entrepreneurship for such communities. The first case delineates the problems of local communities and the need for resource conservation and defines the potential of tourism-based entrepreneurship to preserve cultural, historical, and environmental heritage in such communities. The second case describes the challenges of marginalized communities to improve the quality of life and remarks on the possibilities of tourism-based social entrepreneurs to deal with agri-food practices and establish social wealth for such social groups. The third case indicates the type of pro-poor tourism concept and its opportunities to support and regenerate impoverished communities through effective collaboration, biodiversity support and eliminating social exclusion and extreme poverty.